Intravesical foreign body and transitional cell carcinoma in a dog. Issue 1 (11th November 2015) - Rainer, Johanna; Neiger, Reto
Abstract : A nine‐year‐old chemically neutered male hovawart was referred due to dysuria, stranguria, haematuria and inappetence. Initial examinations suggested a transitional cell carcinoma of the urinary bladder with pulmonary metastases and ureteral ectopia. To confirm the diagnosis and rule out possible ureteral ectopia, cystoscopy was performed. Transitional cell carcinoma was confirmed, and a urethral foreign body was revealed. After successful removal, the foreign body turned out to be a 17‐cm long piece of a urinary catheter. The dog's clinical signs ceased completely a few days after extraction of the foreign object and palliative therapy with meloxicam. Approximately four weeks later its condition deteriorated and the owner elected euthanasia.